Комп'ютерне моделювання індуктивного елемента планарної системи - Андрійчук, В.А.; Наконечний, М.С. (Технічна електродинаміка, 2015)
Проведено комп'ютерне моделювання індуктивного елемента планарної системи з використанням магнітного середовища нікель-цинкового фериту. На основі розв'язаної вісесиметричної задачі одержано залежності зміни індуктивності та добротності планарного елемента від частоти та показано вплив геометричних розмірів моделі на ці параметри. Доведено, що запропонована конструкція магнітопроводу дозволяє одержувати необхідну індуктивність та добротність планарного елемента за заданих геометричних розмірів. Проведено компьютерное моделирование индуктивного элемента планарной системы с использованием магнитной среды никель-цинкового феррита марки CDM 5005. На основе решенной осесимметричной задачи получены зависимости изменения индуктивности и добротности планарного элемента от частоты и показано
влияние геометрических размеров модели на эти параметры. Показано, что предложенная конструкция магнитопровода позволяет получать необходимую индуктивность и добротность планарного элемента при заданных геометрических размерах. In this paper, the authors considered the most common types of planar magnetic inductive elements, and analyzed their
advantages and disadvantages. Actuality use this type of inductive elements as ballasts of fluorescent lamps. A computer
simulation of inductive element planar system using magnetic environment nickel-zinc ferrite brand CDM 5005
Based unleashed axisymmetric problem is obtained depending on changes in inductance and quality factor of a planar
element frequency, and the influence of geometrical dimensions of the model to these parameters. It is shown that fill
the space between the turns of the coil inductance increases by more than half. and reduce the size of inductive elements
more than three times. Due to the reduced length of the conductive material decreases the resistance of the coil. The
calculation of the magnetic characteristics of the ballast using a computer model makes it possible to simplify the selection
of non-magnetic gap size.